The broadening of SOL profiles in JET tritium plasma and its impact on machine operation. (1st January 2023) - Sun, H.J.; Silburn, S.A.; Carvalho, I.S.; King, D.B.; Giroud, C.; Fishpool, G.; Matthews, G.F.; Henriques, R.B.; Keeling, D.L.; Rimini, F.G.; Garzotti, L.; Frigione, D.; et al.
Abstract: Unusually high power loads on the beryllium limiter caused by neutral beam re-ionisation, and much cooler divertor target surfaces were observed during the recent JET tokamak tritium campaign. As both phenomena are driven by scrape-off layer (SOL) physics, the SOL features of 72 tritium H-mode discharges and their deuterium references have been studied. The majority (70) of tritium H-mode discharges had exponentially decaying SOL profiles. The tritium plasmas are observed to have increased separatrix density and collisionality compared to their deuterium references. This is associated with ≈ 2 − 3 times broader SOL width for both density and temperature profiles. This is consistent with previous observations in highly collisional deuterium H-mode plasma on the ASDEX Upgrade tokamak (Sun et al 2015 Plasma Phys. Control. Fusion 57 075005) and interpreted as high collisionality enhancing cross-field transport across the separatrix and resulting in the broadening of near SOL above a critical value. The other two tritium H-mode discharges had near flat SOL density profiles, similar to the so-called ' density shoulder formation ' observed in L-mode plasma. The SOL collisionality of these two pulses lies within the range of T pulses without density shoulder formation. This supports the conclusion of previous studies (Vianello et al 2017 Nucl. Fusion 57 116014; Wynn et al 2018 Nucl. Fusion 58 056001) that increased collisionality is not sufficient for the formation of a ' density shoulder ' and additional factors, likely divertor condition or interaction with neutrals, are required. JET tritium plasma provides evidence of favourable and unfavourable effects of enhanced cross-field SOL transport on machine operation. The larger limiter power loads due to re-ionisation of neutral beam injection observed in the T pulses relative to their D references has been shown to be consistent with the combined effects of the broadening of the SOL profile and larger beam ion Larmor radius. The enhanced cross-field particle transport and the resulting broader SOL width provides more particles to ionize the fast Beam neutrals, causing the unfavourable power load issue on the beryllium limiter. The broader near SOL profiles of the T plasma spreads the heat load over a larger area and, together with the increased separatrix density, results in a favourably cooler divertor target surface.